The abscopal effect of immune-radiation therapy in recurrent and metastatic cervical cancer: a narrative review - Ollivier, Luc; Moreau Bachelard, Camille; Renaud, Emmanuelle; Dhamelincourt, Estelle; Lucia, Francois (Frontiers in Immunology, 2023)
Despite human papillomavirus vaccination and screening, in about 5% of cases, cervical cancer (CC) is discovered at an initial metastatic stage. Moreover, nearly one-third of patients with locally advanced CC (LACC) will have a recurrence of their disease during follow-up. At the stage of recurrent or metastatic CC, there are very few treatment options. They are considered incurable with a very poor prognosis. For many years, the standard of care was the combination of platinumbased drug and paclitaxel with the possible addition of bevacizumab. The most recent years have seen the development of the use of immune checkpoint inhibitors (ICIs) (pembrolizumab, cemiplimab and others) in patients with CC. They have shown long term responses with improved overall survival of patients in 1st line (in addition to chemotherapy) or 2nd line (as monotherapy) treatment. Another emerging drug is tisotumab vedotin, an antibody-drug conjugate targeting tissue factor. Radiation therapy (RT) often has a limited palliative indication in metastatic cancers. However, it has been observed that RT can induce tumor shrinkage both in distant metastatic tumors beyond the radiation field and in primary irradiated tumors. This is a rarely observed phenomenon, called abscopal effect, which is thought to be related to the immune system and allows a tumor response throughout the body. It would be the activation of the immune system induced by the irradiation of cancer cells that would lead to a specific type of apoptosis, the